Automated Mapping of Water Bodies from Resourcesat-2 Awifs Image Using Automated Algorithm, Nalgonda District, Telangana State, India. - M. Ganesh, K; A.R.K.Raju, P; S. Satya Vara Prasad, A; Ratnagiri, D (International Journal of Engineering and Technology, 2018)
In the recent past lot of research is taken place on surface water features. The surface water includes lakes, ponds, rivers, streams and other exposed inland water bodies. The function of rainfall amounts, intensity of rainfall etc. over season / year are the variation in spatial extent of these features.  Remote sensing providing lot of data and extracting lot of information over the changes from time to time. Nowadays the role of satellite image process is widely used in extraction of water bodies. Different researchers are using various methods to delineate water bodies from different satellite imagery varying in characteristics like spatial, spectral, and temporal. In FCC water bodies appear as different hues depending on their physical characteristics such as depth of water (bottom reflection), turbidity, etc. Water appears dark due to which absorbs all infrared radiations which helps in easy contrast distinction between water and land in near-infrared band.  Our present area of interest includes an automatic approach to capture the water body from a Resourcesat-2 AWiFS (Advanced Wide-Field Sensor) imagery using a Automated Algorithm for extraction of surface water bodies model. The dynamics of surface water bodies in Study on geospatial analysis of the extraction of water feature sheets for the month of January month 2018 of the study area.  Geospatial database on water bodies information has been created from the Resourcesat-2 AWiFS image. By using bands of 1.55- 1.70 µm (SWIR), 0.77-0.86 µm (NIR), 0.62-0.68 µm (Red) and 0.52-0.59 µm (Green) for the estimation of the water spread area.  The Water spread area (WSA) calculated for each is 37231 ha [1] and [2].